Assessment of the effect of left atrial cryoablation enhanced by ganglionated plexi ablation in the treatment of atrial fibrillation in patients undergoing open heart surgery - Bárta, Jiří; Brát, Radim (Journal of cardiothoracic surgery, 2017)
BACKGROUND: The aim of our study was to investigate, whether enhancement of left atrial cryoablation by ablation of the autonomic nervous system of left atrium leads to influencing the outcomes of surgical treatment of atrial fibrillation in patients with structural heart disease undergoing open-heart surgery. METHODS: The observed patient file consisted of 100 patients, who have undergone a combined open-heart surgery at our department between July 2012 and December 2014. The patients were indicated for the surgical procedure due to structural heart disease, and suffered from paroxysmal, persistent, or long-standing persistent atrial fibrillation. In all cases, left atrial cryoablation was performed in the extent of isolation of pulmonary veins, box lesion, connecting lesion with mitral annulus, amputation of the left atrial appendage and connecting lesion of the appendage base with left pulmonary veins. Furthermore, 35 of the patients underwent mapping and radiofrequency ablation of ganglionated plexi, together with discision and ablation of the ligament of Marshall (Group GP). A control group was consisted of 65 patients without ganglionated plexi intervention (Group LA). The main primary outcome was establishment and duration of sinus rhythm in the course of one-year follow-up. RESULTS: Evaluation of the number of patients with a normal sinus rhythm in per cent has shown comparable values in both groups (Group GP - 93.75%, Group LA - 86.67%, p = 0.485); comparable results were also observed in patients with normal sinus rhythm without anti-arrhythmic treatment in the 12th month (Group GP - 50%, Group LA - 47%, p = 0.306). We have not observed any relation between the recurrence of atrial fibrillation and the presence of a mitral valve surgery, or between the presence of a mitral and tricuspid valves surgery and between the left atrial diameter > 50 mm. CONCLUSIONS: Enhancement of left atrial cryoablation by gangionated plexi ablation did not influence the outcomes of surgical ablation due to atrial fibrillation in our population in the course of 12-month follow-up. TRIAL REGISTRATION: The study was approved retrospectively by the Ethics Committee of the University Hospital Ostrava ( reference number 867/2016).
Keywords: senioři; ganglia autonomní; Open-heart surgery; Ganglia, Autonomic; Heart Diseases; Male; nemoci srdce; ganglionektomie; mužské pohlaví; Cardiac Surgical Procedures; Cryosurgery; Ganglionated plexi; Atrial fibrillation; ablace; Left atrial cryoablation; kryochirurgie; ženské pohlaví; Humans; kardiochirurgické výkony; fibrilace síní; Ablation Techniques; Female; Aged; Atrial Fibrillation; lidé; Ganglionectomy